Effects of a whole body compression garment on markers of recovery after an intense whole body resistance training workout in women - Fragala, M. S. (The Journal of Strength and Conditioning Research, 2010)
The primary purpose of this investigation was to evaluate the influence of a whole body compression garment on recovery from a typical heavy resistance training workout in resistance trained women. Nine resistance trained women [mean +/- SD, age (yr) 23.1 +/- 2.2, height (cm) 161.6 +/- 6.2, body mass (kg) 59.5. +/- 5.5] gave informed consent to participate in the study. A within-group [each subject acted as their own control], balanced and randomized treatment design was used. A whole body heavy resistance exercise protocol using barbells [3sets 8-10 RM, 2.0-2.5 min rest] consisting of a back squat, bench press, stationary lunge, bent over row, Romanian dead lift, biceps curl, sit-ups and high pull from a hang was performed after which the subject showered and put on a whole body compression garment (CG) (75% Nylon and 25% Spandex,) or just wore her normal non-compression clothing (CON). Subjects were then tested 24 hr later in the laboratory immediately after they removed the compression garment and put on their workout attire on in order to determine recovery differences between conditions. Nutritional intakes, activity, and behavioral patterns (e.g., no pain medications, ice or long showers over the 24 hr) were replicated with test protocol sequences separated by 72 hours. Dependent measures included, sleep quality, vitality rating, resting fatigue rating, muscle soreness, muscle swelling via ultrasound, reaction movement times, bench throw power, countermovement vertical jump power (CMVJ), and serum concentrations of creatine kinase (CK) measured from a blood sample obtained via venipuncture of an arm vein. An analysis of variance was used to determine differences between treatments and p <=0.05 was defined as significance in this study. There was no significant difference in sleep quality between conditions; vitality rating, with 7 the highest rating, the CG [6.0 + 0.6]was significantly higher than CON [3.2 + 0.6], resting fatigue was significantly lower in CG [1.86 + 1.28] vs CON [3.58 + 1.84], muscle soreness was significantly lower in CG [1.52 + 0.56] vs CON [2.92 + 1.34], muscle swelling was significantly lower in CG [19.3 + 1.3 cm] vs CON [21.7 + 1.2, cm], no differences were observed in reaction/movement time, bench press throw power was significantly higher in CG [239.5 + 56.3 W] vs CON [173.2. + 18.5 W], no differences for CMVJ, and resting CK was significantly lower in CG [119.1 + 52.9 IU/L] vs CON [266.6 + 185.6 IU/L]. A whole body compression garment worn during the 24 hr recovery period after an intense heavy resistance training workout enhances various psychological, physiological and performance markers of recovery compared to control garment conditions. The use of compression has been previously shown to help athletic performance, reduce damage from soft tissue injury and now it appears that compression can help in the recovery process from an intense resistance training workout in women.